Challenging and solutions in attracting and retaining millennial employees during environmental disruption: a developing country perspective - Islam, Md Asadul; Haque, A. K. M. Ahasanul; Hossain, Md Shahadat (Publication Unit, Faculty Economics and Business, Universitas Gadjah Mada, 2020)
Environmental disruption is called an ecological situation where people experience life-threatening changes in their living conditions. A livid example of such an environmental disruption is the COVID-19 pandemic, which impacts our personal and professional life. This pandemic is not only responsible for the high unemployment but also for a lack of confidence among different employees to the employers. This is very much alarming for the millennial i.e. generation Z employees, who always show high turnover intention and tend to leave organisations not only to join in other organisations but also to create something new for themselves to be independent. In the initial stage of the COVID-19 pandemic i.e. current environmental disruption, many organisations among 4621 registered factories of this industry retrenched employees in a large scale that has created a negative impression on potential and skilled employees especially among millennials (70% of the total workforce are millennials among 4.1 million workers in the industry). It is because they had to close their operations to maintain government lockdown policies, therefore, they had to laid-off employees. In addition, orders from the western buyers sharply reduced due to the COVID-19 pandemic, therefore, many employees had to leave their organisations without any future. However, now even during the pandemic orders from western buyers have been increased dramatically especially after the withdrawal or reduction of lockdown rules and regulations in Bangladesh and other countries. Therefore, to cope with extra works in RMG factories due to increased orders from buyers, the factories have to attract and retain the millennials, who are already confused to join in the industry from where many of them were forced leave. Existing literature is mainly dearth about the processes and arrangements that can attract skilled millennials and retain them during current and post environmental disruption especially in a country with more millennials workers in the total workforce